Mortality and cancer morbidity in cohorts of asbestos cement workers and referents. Issue 9 (September 1990) - Albin, M; Jakobsson, K; Attewell, R; Johansson, L; Welinder, H
Abstract : Total and cause specific mortality and cancer morbidity were studied among 1929 asbestos cement workers with an estimated median cumulative exposure of 2.3 fibre (f)-years/ml (median intensity 1.2 f/ml, predominantly chrysotile). A local reference cohort of 1233 industrial workers and non-case referents from the exposed cohort were used for comparisons. The risk for pleural mesothelioma was significantly increased (13 cases out of 592 deaths in workers with at least 20 years latency). No case of peritoneal mesothelioma was found. A significant dose response relation was found for cumulative exposure 40 years or more before the diagnosis, with a multiplicative relative risk (RR) of 1.9 for each f-year/ml. No relation was found with duration of exposure when latency was accounted for. There was a significant overrisk in non-malignant respiratory disease (RR = 2.6). The overall risks for respiratory cancer, excluding mesothelioma, and for gastrointestinal cancer were not significantly increased. Surprisingly, colorectal cancer displayed a clear relation with cumulative dose, with an estimated increase of 1.6% in the incidence density ratio for each f-year/ml (but not with duration of exposure).